Resident support for tourism: Does religiosity matter? - Kayat, Kalsom; Abdul Ghani, A.; Ahmad, S. A. (American Scientific Publishers, 2015)
For tourism to become a sustainable development strategy, support from the residents is needed.Past research have shown different factors such as residents’ socio demographic characteristics and their cultural structure may influence their dispositions toward tourism, thus influencing their support toward tourism development.This paper is about establishing a conceptual framework of tourism participation by residents in Aceh Province who are characterized by Islamic law and culture.To this end, previous research and writings on community participation, tourism and religion are reviewed and analyzed.The paper concludes with propositions for future studies in exploring Aceh resident support for tourism.